A stepped-wedge randomised-controlled trial assessing the implementation, impact and costs of a prospective feedback loop to promote appropriate care and treatment for older patients in acute hospitals at the end of life: Study protocol - Lee, X.J. (BioMed Central, 2021)
10.1186/s12877-020-01660-2